Popularity of FM radio advertisements in Bangladesh: current attractiveness and the future - Shejuti, Asma-Ul-Husna (BRAC University, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.